Malaria Seroprevalence in the Blood Donors of Malaria Endemic Regions of Northern Andhra Pradesh, India. - Dr. C. Sitalata; Dr. K. Kalyan (Tropical Journal of Pathology and Microbiology, 2020)
Introduction: Transmission of malaria through blood transfusion continues to be a major threat to safe blood transfusion practice. Transfusion-transmitted malaria occurs at an estimated rate of 0.25 cases per 1 million blood units collected. It is significantly more common in endemic areas.AIM: To study the Seroprevalence of Malaria among the blood donors in the endemic areas of Northern Andhra Pradesh.Materials and methods: The present survey was carried out at the blood bank of Maharaja institute of medical sciences, Vizianagaram. This includes the analysis of seroprevalence of Malaria in the blood donors during the period of 1 year from February 2018 to January 2019. Two ml of the blood sample was collected in the labeled pilot tube at the time of collection of blood from donor tubing of the blood bag. The serum was separated. The samples were tested for Malaria by rapid antigen detection test.Results: Out of the total of 3096 blood donors, replacement donors (86.91%) were more in comparison to voluntary donors (13.08%). The seroprevalence among the replacement blood donors was more compared to voluntary blood donors.Conclusion: Voluntary blood donation, increasing awareness about blood donation in the general population, selection of repeat, non-remunerated, regular voluntary blood donors and diligent donor selection, sensitive screening tests are most important to increase blood safety and prevent transmission of Malaria through blood transfusion.